KEBIJAKAN PEMBANGUNAN SEKTOR PARIWISATA DI KALIMANTAN SELATAN, KESEJAHTERAAN SOSIAL DAN KEMANDIRIAN MASYARAKAT MISKIN - Rahmini, Noor (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
This study aims to determine the policy of tourism development in reducing poverty.This research is a qualitative research. The research site is set in South Kalimantanwhich includes all tourist attractions in South Kalimantan in 13 regencies/cities.The focus of research is conducted at leading tourist attraction in South Kalimantan.The population of this research includes all Tourism Departments in South Kalimantanof 13 regencies/cities and community figures at the tourist attractions. The samplingtechniques use purposive sampling and snowball sampling. This is done because ofthe number of data sources did not give a satisfactory data, so the researchers foundthe others that can be used as the source of data (Sugiyono, 2007). The data collectionis conducted through interviews, observation, and study of documentation. The datathat has been obtained is analyzed by using interactive model of analysis which wasdeveloped by Miles and Huberman (1992). This interactive data analysis consists ofthree components; they are reduction, data presentation, and conclusion.Keywords: tourism, tourist attraction, multiplier effect, poverty